Caracterização físico-química e por infravermelho próximo de diferentes tipos de almeirão-de-árvore (Lactuca cf canadensis L.) em função do período de armazenamento - Mendes, Marcelo Henrique Avelar (2021)
The Lactuca cf canadensis L. is a leafy, erect and vigorous non-conventional vegetable, known to be largely polymorphic with different morphotypes. Thus, the objective of the study was to analyze the physical and chemical characteristics of the four morphological types ofLactuca cf.canadensis L. in storage conditions and correlate the results obtained in the laboratory with the spectra obtained in the analysis of near infrared spectroscopy (NIR). The physico-chemical parameters analyzed were: Total Soluble Solids (SST), Total Titratable Acidity (ATT), Ratio (SST / ATT), pH, Monomeric anthocyanins, Vitamin C, Total Phenolic Compounds, Total Carotenoids, DPPH and Coloring. These parameters were analyzed every two days, totaling ten days of storage (0 days; 2 days; 4 days; 6 days; 8 days and 10 days). The experimental design in the laboratory was completely randomized, with three replications in triplicates. The spectra were collected following the storage days, totaling 9 readings for each treatment. The laboratory results were subjected to analysis of variance and Scott & Knott average test, with the aid of the SISVAR® software. The data from near infrared spectroscopy were evaluated using principal component analysis (PCA) and partial least squares regression analysis (PLS-R), with the help of the Chemoface® statistical software. Laboratory analyzes showed a significant difference between the types of Lactuca cf canadensis L. during storage, with an increase in the levels of Total Soluble Solids, variation of the Total Titratable Acidity levels, an increase in the pH and Total Carotenoids, a drop in the Vitamin contents C, Anthocyanins and Total Phenolic Compounds, and consequently color variation, indicating depreciation in leaf quality